Antimicrobial, Antioxidant Activity and Phytochemical Screening of Tecoma stans (L.) Juss. ex Kunth. - Channabasava R1, Jeevitha MK2, Pooja KS2 and Vinay B. Raghavendra3, Govindappa M1*, Sadananda TS1 (Journal of Phytology, 2011)
The ethanol, methanol and water extracts of Tecoma stans effective against tested bacteria (Pseudomonas fluorescens, Clavibacter michiganensis sub sp. michiganensis, Xanthomonas axanopodis pv. malvacearum, Staphylococcus aureus, E. coli, Pseudomonas aeruginosa and Klebsiella pneumonia) and fungi (all species of Aspergillus and Alternaria). Phytochemical analysis revealed the presence of alkaloids, flavonoids, saponins, phenols, steroids, anthraquinones and tannins. The three extract fractions have showed highest total Phenolic content (177-216 mg gallic acid equivalent/g). These three solvent fractions possessed strong radical scavenging activity from FRAP and DPPH. It was ranged from 1433.75 to 3841.17 g/ml. The results indicate that this plant is a potential candidate to be used as an antimicrobial and antioxidant. Key words: Tecoma stans, Antimicrobial, antioxidant, phytochemicals <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Govindappa M et al. Antimicrobial, Antioxidant Activity and Phytochemical Screening of Tecoma stans (L.) Juss. ex Kunth. J Phytol 3/3 (2011) 68-76.